Contradictory Role of Forgiveness against Undergraduate Students’ Online Game Addiction Tendency: Two Preliminary Studies Before and During the COVID-19 Pandemic - Rahmandani, Amalia (Jurnal Kajian Bimbingan dan Konseling, 2025)
Two quantitative and cross-sectional preliminary studies were conducted to address the issues of forgiveness in the context of the tendency to online game addiction among university students in Semarang, Indonesia. A forgiveness scale comprising three dimensions of forgiveness, including forgiveness of self, others, and situations, as well as two separate scales of the tendency to online game addiction, was used. Samples consisting of two groups of online gamers were obtained using a convenience sampling technique. The sample size of Study 1, conducted prior to the onset of the COVID-19 pandemic, was 114 participants (Male = 98.25%) from four game centers. Meanwhile, Study 2, which was carried out during the COVID-19 pandemic, examined 25 participants (Male = 88%) from a university esports community. Based on the assumption tests, the data were analyzed separately using Spearman’s rho (Study 1) and partial correlation (Study 2), resulting in contradictory results. In Study 1, only one dimension of forgiveness demonstrated a positive contribution, namely forgiveness of others. In contrast, the findings of Study 2 indicated that forgiveness in general and, in particular, forgiveness of others and forgiveness of situations, had a negative impact. Furthermore, differences in forgiveness between dimensions and between samples were also investigated. The results indicated the peculiarities of self-forgiveness. To understand the patterns of the contribution of forgiveness to the tendency to non-substance addictions, particularly online games, among university students, further studies on this topic may consider the globally accepted online gaming behavior, usage motivation, and game genres, level of a tendency to addiction, awareness of transgressions faced, and the burdens borne.